Evaluation of a mixture of creolin, molasses and ashes against the coffee berry borer, Hypothenemus hampei (Coleoptera: Seolitydae) and some of its natural enemies - ZENNER DE POLANÍA, INGEBORG; QUINTERO, JOHANNA; QUINTERO, FREDDY (Revista Colombiana de Entomología, 2001)
Since 1988, when the coffee berry borer, Hypothenemus hampei (Ferrari) was registered in Colombia, CENlCAFE started research to provide its management, existing actually a very satisfactory program. This lPM is however considered by some coffee growers too costly, therefore they revert to home remedies. One of these corresponds to the use of a mixture of creolin, molasses, and ashes. Before rejecting the use, it had to be evaluated. which was the objective of this research. In a var. Colombia coffee plantation, at Anolaima (Cundinamarca), the behavior of the mixture, in different proportions and spray schedules, regarding the coffee berry borer and its naturally existing enemies was estímated. using a random plot design with three repetitions. Each plot consisted of three furrows of ten coffee plants. Coffee berry borer infestation and adult mortality by natíve entomophagous fungi were determined weekly on the berries of three marked branches located in the median part of three trees of the central row. Simultaneously 50% of the attacked berries of two branches of six trees, chosen randomly per plot, were collected to observe the effect of the mixture on the immatures of the pest. Predatory ant population was estimated using traps baited with sausage. Based on the results it was concluded that the mixture does not control the coffee berry borer, neither affects the immatures of the insect. No negative influence on the existing natural enemies, a complex of the fungi Fusarium sp. and Beauveria bassiana and the predatory ant Pheidole pos. biconstricta, was detected.